International External Validation Study of the 2014 European Society of Cardiology Guidelines on Sudden Cardiac Death Prevention in Hypertrophic Cardiomyopathy (EVIDENCE-HCM). Issue 10 (6th March 2018) - O'Mahony, Constantinos; Jichi, Fatima; Ommen, Steve R.; Christiaans, Imke; Arbustini, Eloisa; Garcia-Pavia, Pablo; Cecchi, Franco; Olivotto, Iacopo; Kitaoka, Hiroaki; Gotsman, Israel; Carr-White, Gerald; Mogensen, Jens; et al.
Abstract : Background: Identification of people with hypertrophic cardiomyopathy (HCM) who are at risk of sudden cardiac death (SCD) and require a prophylactic implantable cardioverter defibrillator is challenging. In 2014, the European Society of Cardiology proposed a new risk stratification method based on a risk prediction model (HCM Risk-SCD) that estimates the 5-year risk of SCD. The aim was to externally validate the 2014 European Society of Cardiology recommendations in a geographically diverse cohort of patients recruited from the United States, Europe, the Middle East, and Asia. Methods: This was an observational, retrospective, longitudinal cohort study. Results: The cohort consisted of 3703 patients. Seventy three (2%) patients reached the SCD end point within 5 years of follow-up (5-year incidence, 2.4% [95% confidence interval CI, 1.9–3.0]). The validation study revealed a calibration slope of 1.02 (95% CI, 0.93–1.12), C-index of 0.70 (95% CI, 0.68–0.72), and D-statistic of 1.17 (95% CI, 1.05–1.29). In a complete case analysis (n= 2147; 44 SCD end points at 5 years), patients with a predicted 5-year risk of <4% (n=1524; 71%) had an observed 5-year SCD incidence of 1.4% (95% CI, 0.8–2.2); patients with a predicted risk of ≥6% (n=297; 14%) had an observed SCD incidence of 8.9% (95% CI, 5.96–13.1) at 5 years. For every 13 (297/23) implantable cardioverter defibrillator implantations in patients with an estimated 5-year SCD risk ≥6%, 1 patient can potentially be saved from SCD. Conclusions: This study confirms that the HCM Risk-SCD model provides accurate prognostic information that can be used to target implantable cardioverter defibrillator therapy in patients at the highest risk of SCD. Abstract : Supplemental Digital Content is available in the text.